"Life with an incomplete bite" – Preventive oral care and findings of a child with pre-existing 'Poland syndrome'. Issue 3 (December 2016) - S, Ghousia; K S, Uloopi; Chandrappa, Vinay
Abstract: Background: Poland syndrome is a rare syndrome named by Patrick Clarkson in 1962 and described by Sir Alfred Poland in 1841. Case report: The dental anomalies with pre-existing poland syndromic child were noticed by the parents during child's regular eating-chewing more obviously, after the appearance of his primary teeth. Follow-up: The patient is under oro-myofunctional therapy with other strict preventive regimen and is still being monitored every 6 months since last 2 years. Conclusion: Specific attention must be paid to children with pre-existing conditions with preventive measures and implementation of muscular training very early in life.